Bringing financial stability into monetary policy - Eric Michael Leeper; James Michael Nason (Sveriges Riksbank, 2015)
This paper arms central bank policy makers with ways to think about interactions between financial stability and monetary policy. We frame the issue of whether to integrate financial stability into monetary policy operating rules by appealing to the observation that in actual economies financial markets are incomplete. Incomplete markets create financial market frictions that prevent economic agents from perfectly sharing risk; in the absence of frictions, financial (in)stability would be of no concern. Overcoming these frictions to improve risk sharing across economic agents is, in our view, the intent of policies geared toward ensuring financial stability. There are many definitions of financial stability. Although the de.nitions share the notion that financial stability becomes an issue for policy makers when a breakdown in risk-sharing arrange- ments in financial markets has a negative effect on real economic activity, we give several examples that show this notion is too general for thinking about the role monetary policy might have in smoothing shocks to financial stability. Examples include statistical models that seek to separate "good" from "bad" changes in private-sector debt aggregates, new Keynesian policy prescriptions grounded in neo-Wicksellian natural rate rules, and a historical episode involving the 1920s Federal Reserve. These examples raise a cautionary flag for policy attempts to control the growth and the composition of debt that financial markets produce. We conclude with some advice for revising central banks' Monetary Policy Reports.
Keywords: E3; E4; E5; E6; G2; N12; 330; Financial frictions; incomplete markets; crises; new Keynesian; natural rate; monetary transmission mechanism